Speech, writing, and thought presentation in 19th-Century narrative fiction: a corpus-assisted approach - Busse, Beatrix (Oxford University Press, 2020)
This book investigates speech, writing, and thought presentation in a corpus of 19th-century narrative fiction. Beatrix Busse develops a new corpus-stylistic approach for analyzing and automatically identifying historical strategies of discourse presentation. On the basis of the identification of these diachronic patterns and their positioning in cultural-historical context, Busse shows how discourse presentation furthers narrative progression and shapes readers' expectations.
Keywords: 1800-1899; Geschichte 1800-1900; Sprachstil; Literatur; Englisch